Optimization of removal condition of dye (Basic Red 46) by duck eggshell - Mohd Faizal Salehuddin (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The objective of this study is to investigate the removal of Basic Red 46 (BR 46) by duck eggshell. Dye is a hazardous substance that is found in effluents from the textile industry that must be treated. The presence of dyes in wastewater causes significant damage to the ecological system of water and creates a lot of human disturbance to water resources. This experiment is conducted by identifying the characteristics of untreated duck eggshell and treated duck eggshell using acid. Surface morphology was also studied using scanning electron microscopy (SEM). The operating parameters studied include adsorbent dosage, agitation speed and initial dye concentration. Experiments have been conducted by screening of three parameters. Results of the study parameters for elimination range is 0.5-1.0 g for adsorbent dosage, agitation speed 100-180 rpm and the initial concentration of dye in the range of 50-100 mg/L. Elimination of the highest ranges of the three parameters will be studied using the software "Design Expert". Optimization of adsorption study was carried out using Central Composite Design (CCD) to study the surface response for three parameters. Data showed optimum adsorption condition of Basic Red 46 (BR 46) by the duck eggshell was found at adsorbent dosage, agitation speed and initial dye concentration of 1.0 g, 145.08 and 50.17 mg/L respectively.